Dismissal of potable water from nitrate by means of probiotics - Gvozdyak, P.I.; Sapura, E.V.; Kovalenko, V.F.; Bolgova, E.S.; Demchyna, V.P. (Reports of the National Academy of Sciences of Ukraine, 2014)
We have investigated the purification of potable water from nitrate by means of probiotic bacteria Bacillus subtilis, B. licheniformis, as well as Lactobacillus acidophilus, L. bifidus, L. bulgaricus, and Streptococcus thermophilus, which form a part of corresponding medical preparations. It is shown that the slow (0.1 m · h−1) filtration of water with contents 300–500 mg · l−1 of nitrate through grains of sand and activated carbon or the chemical fiber under the pretext of carrier "VIYA" with immobilized probiotic bacteria on them led to a reduction of the nitrate concentration below 2.5 mg · l−1. Ethanol (0.1 ml to each 100 mg KNO3) was added to treated water to support the microbial growth. The denitrification gas consisted of 95–97% of N2, 0.1–0.3% – CO2, sometimes C2H4(<1%), and (2–3%) – H2O and did not contain H2, CH4, H2S. The biotests showed a high quality and safety of obtained water.